Genetic alterations in poorly differentiated and undifferentiated thyroid carcicomas - Soares, Paula (2011)
Thyroid gland presents a wide spectrum of tumours derived from follicular cells that range from well differentiated, papillary and follicular carcinoma (PTC and FTC, respectively), usually carrying a good prognosis, to the clinically aggressive, poorly differentiated (PDTC) and undifferentiated thyroid carcinoma (UTC). It is usually accepted that PDTC and UTC occur either de novo or progress from a pre-existing well differentiated carcinoma through a multistep process of genetic and epigenetic changes that lead to clonal expansion and neoplastic development. Mutations and epigenetic alterations in PDTC and UTC are far from being totally clarified. Assuming that PDTC and UTC may derive from well differentiated thyroid carcinomas (WDTC), it is expected that some PDTC and UTC would harbour genetic alterations that are typical of PTC and FTC. This is the case for some molecular markers (BRAF and NRAS) that are present in WDTC, PDTC and UTC. Other genes, namely P53, are almost exclusively detected in less differentiated and undifferentiated thyroid tumours, supporting a diagnosis of PDTC or, much more often, UTC. Thyroid-specific rearrangements RET/PTC and PAX8/PPARγ, on the other hand, are rarely found in PDTC and UTC, suggesting that these genetic alterations do not predispose cells to dedifferentiation. In the present review we have summarized the molecular changes associated with the two most aggressive types of thyroid cancer.